Functional outcome of supracondylar fracture femur treated with plate fixation and retrograde intramedullary nailing – A comparative study - Varun Vasudevan; TM Jose; Manesh Philip (Journal of the Bulgarian Orthopaedics and Trauma Association, 2023)
Fractures of distal femur reportedly account for less than 1% of all fractures and about 4% of all femur fractures. Aims of the treatment of extra-articular fractures are restoration of length, torsion, and frontal and sagittal plane alignment and stable fixation. The objective of the study is to compare the functional and radiological outcome of the patients who sustained the distal femoral fractures treated with plate fixation against retrograde intramedullary nail. Patients meeting the specified inclusion criteria were divided into two groups: one treated with retrograde intramedullary nailing and the other with plate fixation. Follow-up assessments were performed at 4, 12, and 24 weeks post-surgery, utilizing flexion scores and Modified Schatzker and Lambert criteria to evaluate functional and radiological outcomes. The functional outcomes and knee flexion scores at the 6-month mark showed no significant difference between the plating and nailing groups. However, the plating group demonstrated early recovery, with a significant improvement in range of motion observed at 4 weeks post-operation. Retrograde intramedullary nailing exhibited advantages in terms of shorter surgery duration and lower intraoperative blood loss, making it a preferred option for patients with anticipated major blood loss or polytraumatized individuals.